ANALISIS PRODUKSI LATEKS PADA PTPN VII WAY BERULU - Eka Fitriani; Zainal Abidin; Muhammad Ibnu (Lampung University, 2013)
This research aims to analyze the factors of production of latex and the efficiency of latex production in PTPN VII Way Berulu. The data used in this research wass monthly time series data (periodical data) in the period 2007-2011. Independent variables consisted of the harvest areas, usage of urea fertilizer, usage of TSP fertilizer, rainfall, and SEM (Scrapping Ethrel Minyak). The data was analyzed using Ordinary Least Square (OLS). The study showed that: (1) the factors that significantly affected the production of latex were the usage of urea (X2), rainfall (X4), and SEM (X5); while the harvest areas (X1) and usage of TSP (X3) had not to effected to the production of latex; (2) the production of latex in PT Nusantara Plantation VII Way Berulu was still inefficient, operating at decreasing return to scale. Keywords : production, latex, efficiency, time serries